Analysis of the Implementation of Payroll Deductions for Civil Servants (ASN) on Zakat Payment Compliance - Rian Kurniawan; Ridwansyah Ridwansyah; Syamsul Hilal (International Journal of Economics and Management Research, 2025)
The purpose of this study is to examine the mechanism of implementing payroll deductions for civil servants (ASN) in South Lampung in relation to zakat payment compliance in South Lampung Regency, as well as to determine whether the payroll deduction mechanism is in accordance with Islamic principles. This research employs a qualitative approach. The results of the study conclude that the implementation of payroll deductions, based on the circular letter from the Regent, has not had an impact on the zakat payment compliance of South Lampung ASN. Moreover, the payroll deduction mechanism does not yet align with the proper conditions for zakat payment. The payroll deduction for South Lampung ASN cannot be considered as genuine zakat, as not all civil servants in South Lampung receive a salary or allowance amounting to seven million rupiah, which is the threshold for professional zakat (zakat on income).